2021
DOI: 10.3389/fendo.2021.692910
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Benign and Malignant Thyroid Nodules and Identifying Lymph Node Metastasis in Papillary Thyroid Cancer by Plasma N-Glycomics

Abstract: BackgroundBiomarkers are needed for patient stratification between benign thyroid nodules (BTN) and thyroid cancer (TC) and identifying metastasis in TC. Though plasma N-glycome profiling has shown potential in the discovery of biomarkers and can provide new insight into the mechanisms involved, little is known about it in TC and BTN. Besides, several studies have indicated associations between abnormal glycosylation and TC. Here, we aimed to explore plasma protein N-glycome of a TC cohort with regard to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…The peaks of MS spectra were manually assigned to N -glycan compositions using the GlycoPeakfinder tool of GlycoWorkbench [ 33 , 34 ]. The N -glycan compositions were also confirmed by previous literature [ 25 , 28 , 29 ]. A detailed process for glycan identification is provided in the Supplementary Materials .…”
Section: Methodssupporting
confidence: 89%
See 4 more Smart Citations
“…The peaks of MS spectra were manually assigned to N -glycan compositions using the GlycoPeakfinder tool of GlycoWorkbench [ 33 , 34 ]. The N -glycan compositions were also confirmed by previous literature [ 25 , 28 , 29 ]. A detailed process for glycan identification is provided in the Supplementary Materials .…”
Section: Methodssupporting
confidence: 89%
“…Aberrant N -glycans in PTC patients (compared to HC) discovered in our previous study [ 25 ] and dysregulated N -glycans in PTMC patients (compared to HC) found in the present study were compared. We found three glycan traits (CA4, CFa, and A2Fa) were both dysregulated in PTC and PTMC.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations